Pharmacological interventions to modulate attentional bias in addiction. (1st August 2013) - Luijten, Maartje; Field, Matt; Franken, Ingmar H. A.
Abstract : Attentional bias in substance-dependent patients is the tendency to automatically direct attention to substance-related cues in the environment. Preclinical models suggest that attentional bias emerges as a consequence of dopaminergic activity evoked by substance-related cues. The aim of the current review is to describe pharmacological mechanisms underlying attentional bias in humans and to critically review empirical studies that aimed to modulate attentional bias in substance-dependent patients by using pharmacological agents. The findings of the reviewed studies suggest that attentional bias and related brain activation may be modulated by dopamine. All of the reviewed studies investigated acute effects of pharmacological agents, while measurements of chronic pharmacological treatments on attentional bias and clinically relevant measures such as relapse are yet lacking. Therefore, the current findings should be interpreted as a proof of principle concerning the role of dopamine in attentional bias. At the moment, there is too little evidence for clinical applications. While the literature search was not limited to dopamine, there is a lack of studies investigating the role of non-dopaminergic neurotransmitter systems in substance-related attentional bias. A focus on neurotransmitter systems such as acetylcholine and noradrenaline could provide new insights regarding the pharmacology of substance-related attentional bias.